Using Interactive Teaching Materials to Improve Indonesian Students' Numeracy Skills: A Systematic Literature Review - Maharani Kartikasari; Triyanto; Laila Fitriana; Farida Nurhasanah (Jurnal VARIDIKA, 2025)
The use of appropriate teaching materials can be used to improve numeracy skills of students in Indonesia. The use of teaching materials at various levels of education in Indonesia is still limited and even if there are not many that are interactive. This research uses the Systematic Literature Review (SLR) method which is guided by PRISMA. The SLR in this article aims to find out the types of interactive teaching materials used to improve numeracy skills at various levels, how they are used and in what materials the use of interactive teaching materials is applied. The articles reviewed are in indexed Indonesian language and specifically contain interactive teaching materials to improve numeracy skills in mathematics learning. Articles were searched using the Publish or Perish application and the Google Scholar database from 2020 to 2024. Based on the inclusion criteria there were 14 articles as primary studies out of 670 articles found. . The conclusion obtained is that the types of interactive teaching materials used to improve the numeracy skills of students at various levels are those that use digital devices or not. The way of utilizing interactive teaching materials to improve numeracy skills can be done independently or integrated with media, models or learning approaches. In general, the use of interactive teaching materials to improve numeracy skills is not specific to certain materials. Educators are recommended to develop interactive teaching materials that are a combination of using digital and non-digital devices to improve students' numeracy skills.